Research progress in traditional Chinese medicine in the treatment of Alzheimer’s disease and related dementias - Tan, Wanying; Qi, Lingjun; Hu, Xiaoyu; Tan, Zhenghuai (Frontiers in Pharmacology, 2022)
Alzheimer's disease (AD) is the world's leading cause of dementia and become a huge economic burden at nations and families. However,the exact etiology of AD is yet unknown and there is no efficient medicines or methods.Traditional Chinese medicine (TCM) has made important contributions in the battle against AD, based on the characteristic of multiple targets of TCM. This study reviewed the treatment strategies and new discoveries of traditional Chinese medicine in the current researches, it maybe beneficial to the new drug researcher.